Information Systems for Business and Beyond - Bourgeois, David T.; Smith, James L.; Wang, Shouhong; Mortati, Joseph (Open textbook library., 2019)
This book is written as an introductory text, meant for those with little or no experience with computers or information systems. While sometimes the descriptions can get a little bit technical, every effort has been made to convey the information essential to understanding a topic while not getting bogged down in detailed terminology or esoteric discussions. Information Systems for Business and Beyond was written by Dr. David Bourgeois and originally published in 2014 as part of the Open Textbook Challenge at the Saylor Foundation. Since then, it has been accessed thousands of time and used in many courses worldwide. This 2019 update to the textbook brings it up to date and adds many new topics. True to its open textbook roots, many of the updates have come from the community of instructors and practitioners who are passionate about information systems. Please note that the XML and MS Word links go to an earlier version.